Segara Anakan Lagoon (SAL): Fish Biodiversity and the Ecological Role - Setijanto Setijanto; Siti Rukayah (Journal Omni-Akuatika, 2016)
Two life stages of fish were sampled to examine the fish biodiversity and the ecological role of Segara Anakan lagoon (SAL). The fish were observed in during 2004 – 2014 while the larvae were sampled twice monthly during the full moon and dark periods in daylight hours only over 11 month periods (Novembre 2005 to Septembre 2006) at 10 sites located at SAL, Cilacap. Each trip two samples of the high tide and low ebb periods were taken from each station. The mature fish were sampled at Klaces and Karanganyar. The fish were also collected from fisherman. At least 90 genera of 48 family (65 mature fish and 64 larvae) were recorded at SAL. Gobbidae (range between 67.3 – 72.9 %) and Engraullidae (16.7 – 19.3 %) are the two most abundant larvae captured. Of the fish, at least 40 genera belongs to 16 families are of resident species that inhabit SAL for whole their life cycles. In other hand, 50 genera belongs to 31 families use SAL as temporary habitat (migratory). This finding suggests the important ecological role of SAL for fish.Keywords : segara anakan lagoon, biodiversity, ekological role